TRAINING FOR SOLVING MATHEMATTICS OLYMPIAD QUESTIONS FOR TEACHER AND STUDENTS IN KONAWE: Training For Solving Mathemattics Olympiad Questions For Teacher And Students In Konawe - halistin, halistin; Riansyah, Firman; Patih, Tandri; Ahmad, Hidayat; Riza, Muhammad; Awaliyah, Kurnia (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2025)
Olympiads or academic competitions are one of the forums schools use to measure the quality of learning output provided so far. Olympiads are usually held from district to international levels. However, some students and teachers find it difficult to update or enrich their knowledge in solving Olympiad questions. This results in teachers and students having difficulty when solving Olympiad questions. The strategy that can enhance the material and questions of the Mathematics Olympiad is providing modules of material and Mathematics Olympiad questions and demonstrations of solving Olympiad questions. The PAR (Participatory Action Research) method is the method of implementing this community service. The average value obtained by students was 10.67 out of 100, which means that the initial ability of teachers and students to solve Olympiad questions is still low. Furthermore, 46.7% of teachers and students could not answer a question. Furthermore, the initial ability of teachers and students to use the Olympiad material is still low, namely less than 10%, apart from the number theory material. After mentoring, the average score obtained by students was 22.3 out of 100, which means that the initial ability of teachers and students to solve Olympiad questions increased by around 11.6%. Furthermore, 26.67% of teachers and students could not answer a question. Moreover, the abilities of teachers and students increased in algebra and combinatorics materials. Keywords: Algebra; Combinatorics; Math Olympiad